Database and expert systems applications : 29th International Conference, DEXA 2018, Regensburg, Germany, September 3-6, 2018, Proceedings.: 29th International Conference, DEXA 2018, Regensburg, Germany, September 3-6, 2018, Proceedings. Part II (2018) - Unknown
No abstract available